Peningkatan Kemampuan Keaksaraan Anak Usia Dini melalui Berbagai Media Pembelajaran - Putri, Farah Rizkita (Absorbent Mind, 2022)
Efforts to improve awareness skills through various learning media to improve the child's ability in terms of mentioning known letter symbols, knowing the initial letter sounds from the names of objects around them, mentioning groups of images that have the same initial sounds/letters, understanding the relationship between sounds and letter shapes and writing and reading their names. The method used in this study is class action research. The implementation of class action research is carried out using a cycle system in which there are component planning, action, observation, and reflection. The result of this study is that literacy skills can be stimulated through various learning media. The media used can be objected to that are liked by children, names attached to objects, daily and repeated pronunciation habits. In the observation stage of research, toddlers are involved in active, creative, effective, and enjoyable learning. Media in early childhood learning in the improvement and development of aspects of language development, especially the child's literacy ability in reading letters, distinguishing letters, reading two syllables, and reading words.